(3GdJegjO deG aj GdehWC ef GdeYGfi hGdCSGfjOs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdBNQ GdXGgQ GdHGWf CeG HYO aEfi QCjJ cd ef bUO Edi JNQjL eG ai ehWC eGdc Hf CfS s
(3BNQgG (B:s
(3ef TQM MOjK QGHY dMejO Hf bjS efbWY (B: (3bGd CHh YeQ (B: (3hSjCJi ddQbGA (B[ (3ddQbi (B] (3PcQ ai ehGVY ef gPG GdOjhGf Ydi MSH JcQGQ CMGOjK eGdc Ef TGA Gddg GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs